Contribution of the Godoy Method® to Treat Breast Cancer- Related Lymphedema Running Head: Godoy Method and Breast Cancer (International Journal of Physiotherapy, 2025)
Background: Lymphedema of the arm and chest is one complication of breast cancer treatment. It brings yet another challenge to patients and professionals responsible for their rehabilitation. The study aims to show advances in the treatment of lymphedema using this Godoy technique and your evaluation.Development studies: In recent years, new concepts and contributions to the treatment of breast cancer-related lymphedema have evolved, including the Godoy method. The Godoy method has many facets: new drainage techniques adapted to treat lymphedema after breast cancer treatment, new concepts such as an intensive form of treatment, mechanical lymphatic drainage equipment, new materials for making compression sleeves, a line of research associated with exercises and occupational activities, evaluation of psychological aspects, and the creation of multidisciplinary therapeutic groups.Conclusion: In summary, a set of innovations that improve therapeutic outcomes. This review identifies the fundamental principles of Godoy's method intervention studies for the treatment of lymphedema, ensuring their clinical relevance and providing practicing clinicians not only with a better understanding but also with the ability to implement them in their own studies.